LAND-USE INFLUENCE ON HYPORHEIC BIOTA FROM MEDITERRANEAN STREAMS IN CENTRAL SPAIN - IEPURE, Sanda; KALLACHE, Malaak; RASINES-LADERO, Ruben (Studia Universitatis Babeș-Bolyai Ambientum, 2020)
Detailed knowledge of hyporheic zone (HZ) biota response to change in land use is crucial for understanding the ecohydrological functioning of communities within the river corridors. This paper investigates the response of hyporheic crustacean communities in relation to spatial heterogeneity in water conditions under changes in land use of the alluvial floodplain of the Jarama basin in central Spain. The study is conducted in four streams of the basin under distinct local land-use and water resource protection conditions: i) preserved forested natural sites at river headwaters where critical river ecosystem processes were unaltered or less altered by human activities, and ii) sites with different degrees of anthropogenic impact from agriculture and urban/ industrial activities in the lowland. The results indicate that streams draining forest and semi-natural areas were characterized by cold and pristine hyporheic waters and crustaceans’ communities harbor a well-developed stygobite fraction. Conversely, intensive agricultural practices in the lowland cause nutrient enrichment of hyporheic waters. Thus, this type of land use increases the diversity and abundance of non-stygobites, whereas the abundance of stygobites is decreased. Mixed activities, industrial and urban development and agricultural cause an extreme decline of the crustacean community and/or species loss due to a combined effect of increase of nitrites, ammonia, trace metals and volatile organic compounds, and a deleterious decline of dissolved oxygen reaching hypoxic and/or anoxic hyporheic water conditions. The combined information of spatial variability of hyporheic biota has the potential to improve the understanding of impacts caused by changes in land-uses on HZ water conditions.